A critical exploration of cultural and aesthetic representation of Shandong dialect translation in Red Sorghum - Yu, Yanqing; Ng, Boon Sim; Mamat, Roslina (Academy Publication, 2024)
The translation of the Shandong dialect, specifically in the novel Red Sorghum authored by Mo Yan and translated by Howard Goldblatt, posed significant challenges to both translators and readers due to its local Chinese cultural richness. Previous researches mainly focused on its traditional translation strategies including foreignization and domestication. Exploration of the aesthetic value of dialect and its cultural representations in modern literature is a relatively new area of research yet to be developed. This paper revealed that translation operates in a complicated three-dimensional structure of translator (aesthetic subject), translated text (aesthetic object), and culture (social environment). In the process of translating dialect, the aesthetic experience and the Aesthetic Regulation Devices (ARD) adopted by the translator, as well as the beauty of characterization and symbolization come into play. Therefore, aesthetic values and cultural uniqueness are represented not only on the linguistic, but also on the spiritual level by contrasting the purity of the villagers in rural China and the brutality of the social turbulence that surrounds them. The paper demonstrated that dialect translation involves a multifaceted and dynamic equivalence between source and target language. The research findings indicated that translation techniques of domestication and foreignization are utilized significantly more often (82%) than the strategy of ARD (18%) during the translation process. This imbalance in strategy usage may result in a deficient representation of aesthetic and cultural values. The significance of this study lies mainly in its intention to reconstruct a more effective theoretical paradigm for dialectal translation procedures.